2007
DOI: 10.1136/bjsm.2006.033845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute salbutamol intake during supramaximal exercise in women

Abstract: From these data, acute therapeutic oral intake of Sal seems to induce, irrespective of the subjects' gender, an improvement in performance during a supramaximal exercise--that is, increase in PP and MP. Further studies are necessary to clarify whether the mechanisms involved in the response to intake of Sal are linked to central and/or peripheral pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 24 publications
2
47
0
Order By: Relevance
“…Although stimulation of central alpha 1-adrenergic mechanisms results in secretion of ACTH in man, presumably by increased release of a corticotrophin-releasing factor, beta-2 adrenergic agonist drugs had no effect on the secretion of ACTH at rest (Al-Damluji et al 1987). However, to the best of our knowledge, the effects of salbutamol on ACTH secretion have never been investigated during submaximal exercise, whereas no change was shown in ACTH secretion after supramaximal exercise (Le Panse et al 2007). In the present study, ACTH concentrations during the last 10 min of exercise were significantly decreased after salbutamol intake versus placebo.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although stimulation of central alpha 1-adrenergic mechanisms results in secretion of ACTH in man, presumably by increased release of a corticotrophin-releasing factor, beta-2 adrenergic agonist drugs had no effect on the secretion of ACTH at rest (Al-Damluji et al 1987). However, to the best of our knowledge, the effects of salbutamol on ACTH secretion have never been investigated during submaximal exercise, whereas no change was shown in ACTH secretion after supramaximal exercise (Le Panse et al 2007). In the present study, ACTH concentrations during the last 10 min of exercise were significantly decreased after salbutamol intake versus placebo.…”
Section: Discussionmentioning
confidence: 87%
“…The earlier limited data on the effects of acute salbutamol on GH in humans (Giustina et al 1995;Collomp et al 2005;Le Panse et al 2006) have found acute salbutamol administration to decrease exercise GH concentrations, probably via enhanced somatostatin secretion and/or activity. In healthy subjects, acute b 2 stimulation blunts the physiological GH response to both maximal (Collomp et al 2002) and supramaximal exercise (Le Panse et al 2007). It may than be suggested that a higher intensity of exercise is necessary to reveal a blunted effect of acute salbutamol on GH secretion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As a consequence of the high use, it is widely debated whether beta 2 -agonists enhance performance (Backer et al 2007;Pluim et al 2011;Wolfarth et al 2010;Kindermann 2007). While most studies show no ergogenic effects of inhaled beta 2 -agonists on exercise performance (Wolfarth et al 2010;Pluim et al 2011), oral salbutamol increases muscle strength (van Baak et al 2000), maximal sprint performance (Collomp et al 2005;Le Panse et al 2007;Sanchez et al 2012), and exercise endurance (Collomp et al 2000;van Baak et al 2000). The discrepancies between inhaled and oral administration of beta 2 -agonists on performance are commonly believed to be a consequence of the route of administration (Wolfarth et al 2010;Sanchez et al 2012Sanchez et al , 2013.…”
mentioning
confidence: 95%
“…Performance during a 30 s cycle sprint was enhanced by oral salbutamol (4-8 mg) (Le Panse et al 2007;Collomp et al 2005;Hostrup et al 2014a), with the post-exercise antecubital (Hostrup et al 2014a (Kalsen et al 2014). Inhalation of the β 2 -agonist albuterol (180 µg) increased peak power during a 15 s cycle sprint (Signorile et al 1992), whilst terbutaline inhalation (450 µg) enhanced 30 s cycle sprint power and reduced post-exercise venous (Hostrup et al 2014b).…”
Section: Introductionmentioning
confidence: 99%